A Bibliometric Analysis of Datafication in Education: Trends, Impact and Future Implications - Nining Anggeraini (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2025)
The massive use of digital learning platforms and AI in education has generated large quantities of dataon teacher and student information, online interactions, and teaching and learning practices. This data can be collected, analyzed, and interpreted to improve educational outcomes. Following the interest and attention in this topic, numerous research studies have been conducted to gain a better understanding in this area. Thus, the purpose of this study is to summarize the literature on datafication in education from 2020 to 2024 and to explore the key terms related to its influence on educational practices, and its potential future implications. The method used in this study is a bibliometric analysis. A total of 200 articles were found in Google Scholar through a search using the keywords "datafication in education."The study found that research on datafication in education has grown significantly in recent years. Initially focused on technological aspects, the research has shifted towards practical applications and critical perspectives. Key themes identified include data literacy, AI, and the ethical implications of data use in education. As an implication of this study, this overview aims to assist future research by enriching and expanding the scope of research and encouraging progress in related disciplines. This will contribute to a fuller understanding of the potential benefits and risks of datafication in transforming education.